Approximation schemes for linear differential-difference equations (Neliniini Kolyvannya, 2025)
Schemes for approximating solutions of initial problems for linear differential-difference systems by solutions of Cauchy problems for special systems of ordinary linear differential equations are proposed and substantiated.